Portugal for Chinese Tourists, an e-guide - XiaoXiao, Li (My University, 2019)
This project consists in an electronic guide (e-guide) dedicated to Chinese tourists who are interested and willing to travel to Portugal. This e-guide introduces Portugal to Chinese tourists, filling in an identified cultural gap, and enhancing Chinese tourists’ knowledge about this destination. In this project, Chinese tourists’ travel preferences and demands are analyzed based on two questionnaires (one a priori and one a posteriori). Based on these results, customized tourism information and travel plans were generated. The preparation and development processes of this e-guide are presented in detail in this project. This project is the final work of the Master’s degree in Tourism and Communication, leading to the achievement of the degree of Master by Escola Superior de Hotelaria e Turismo do Estoril, Faculdade de Letras e Instituto de Geografia e Ordenamento do Território.

Neste projeto desenvolveu-se um guia eletrónico (e-guia), destinado a turistas chineses interessados e dispostos a viajar para Portugal. Este guia eletrónico também serve como um meio de apresentação de Portugal aos turistas chineses, preenchendo lacunas culturais identificadas e aumentando o conhecimento dos turistas chineses sobre este destino. Neste projeto, as preferências e exigências de viagem dos turistas chineses são analisadas com base em dois questionários (um a priori e outro a posterior). Com base nesses resultados, foram geradas informações personalizadas sobre turismo e desenvolvidos planos de viagem. Os processos de preparação e desenvolvimento deste guia eletrónico são apresentados em detalhe neste projeto. O projeto corresponde ao trabalho final do Mestrado em Turismo e Comunicação, levando à obtenção do grau de Mestre a atribuir pela Escola Superior de Hotelaria e Turismo do Estoril, pela Faculdade de Letras e pelo Instituto de Geografia e Ordenamento do Território.
Keywords: Tourism; Portugal; Destination; Chinese tourists; Turismo; Destino; Turistas chineses